Complete genome sequence of Bacillus cereus FORC_005, a food-borne pathogen from the soy sauce braised fish-cake with quail-egg. Issue 1 (December 2015) - Lee, Dong-Hoon; Kim, Hye; Chung, Han; Lim, Jong; Kim, Suyeon; Kim, Se; Ku, Hye-Jin; Kim, Heebal; Ryu, Sangryeol; Choi, Sang; Lee, Ju-Hoon
Abstract Due to abundant contamination in various foods, the pathogenesis ofBacillus cereus has been widely studied in physiological and molecular level.B. cereus FORC_005 was isolated from a Korean side dish, soy sauce braised fish-cake with quail-egg in South Korea. While 21 complete genome sequences ofB. cereus has been announced to date, this strain was completely sequenced, analyzed, and compared with other complete genome sequences ofB. cereus to elucidate the distinct pathogenic features of a strain isolated in South Korea. The genomic DNA containing a circular chromosome consists of 5, 349, 617-bp with a GC content of 35.29 %. It was predicted to have 5170 open reading frames, 106 tRNA genes, and 42 rRNA genes. Among the predicted ORFs, 3892 ORFs were annotated to encode functional proteins (75.28 %) and 1278 ORFs were predicted to encode hypothetical proteins (748 conserved and 530 non-conserved hypothetical proteins). This genome information ofB. cereus FORC_005 would extend our understanding of its pathogenesis in genomic level for efficient control of its contamination in foods and further food poisoning.